Holistic vs. Analytic Evaluation in Writing Test of Eighth Grade Students - Elda Selja Putri; Melyann Melani (English Department - University of Sultan Ageng Tirtayasa, 2022)
The purpose of this study is to explore the efficacy of holistic and analytic scoring rubrics when applied to the context of writing examinations. Throughout this research, a technique was utilized to compare two grading models based on (a) assessor agreement (reliability) and (b) reasons for the grades given (validity). Teachers were randomly allocated to one of two conditions, where they graded the same student performance using either an analytical or a holistic approach. The design is experimental. Agreement and rank correlation between grades have been compared. A comparison of the students' performance on a writing assignment is made in this study using both holistic and analytic scoring rubrics. The information for this study was gathered from twenty-four students in eighth grade at SMP N 5 Kecamatan Kapur IX. The authors conducted an analysis of the performance of the students on the two rubrics, using psychometric statistics, in order to precisely determine the strengths and weaknesses of the students, and to place them along a continuum of foreign language writing ability. Citation In contrast, analytic scoring rubrics placed examinees on a scale of writing competency that was more specifically defined. As a result, analytic scoring rubrics were more dependable than holistic scoring rubrics when it came to gauging writing for the purpose of achieving goals.